Contributions of mothers' and fathers' parenting to children's self‐regulation: Evidence from an adoption study. Issue 6 (6th July 2018) - Bridgett, David J.; Ganiban, Jody M.; Neiderhiser, Jenae M.; Natsuaki, Misaki N.; Shaw, Daniel S.; Reiss, David; Leve, Leslie D.
Abstract: The origins of top‐down self‐regulation are attributed to genetic and socialization factors as evidenced by high heritability estimates from twin studies and the influential role of parenting. However, recent evidence suggests that parenting behavior itself is affected by parents' own top‐down self‐regulation. Because children's top‐down self‐regulation is influenced by genetic factors and parenting is influenced by top‐down self‐regulation, the effects of parenting on children's top‐down self‐regulation identified in prior studies may partially reflect passive gene–environment correlation. The goal of this study was to examine parenting influences on children's top‐down self‐regulation using a longitudinal, adoption‐at‐birth design, a method of identifying parenting influences that are independent of the role of shared genetic influences on children's characteristics because adoptive parents are genetically unrelated to their adopted child. Participants ( N = 361) included adoptive families and biological mothers of adopted children. Adoptive mothers' and fathers' harsh/negative parenting were assessed when children were 27 months of age and biological mothers' top‐down self‐regulation was assessed when children were 54 months of age. Adopted children's top‐down self‐regulation was assessed when they were 54 and 72 months of age. Results, accounting for child gender, biological mother top‐down self‐regulation, and the potential evocative effects of adopted child anger, provide evidence that inherited influences and socialization processes uniquely contribute to children's top‐down self‐regulation. Furthermore, findings demonstrate the importance of both mother's and father's parenting behavior as an influence on young children's top‐down self‐regulation. The implications of these findings for understanding the complex mechanisms that influence children's top‐down self‐regulation are discussed. Abstract : Results emphasize the importance of socialization (i.e., maternal and paternal caregiving behavior) and genetic processes as contributors to children's top‐down self‐regulation.